Sosialisasi Menjadikan Generasi Muda Yang Melestarikan Budaya Indonesia Di Desa Suka Damai Timur - Novira Arafah; Syahrul Affan; Rafif Taufiqurrahman; Fathul Mubdhi; Fiqri Handayani (peduli riset dan pengabdian masyarakat, 2025)
The contents of the abstraction, between 150-300 words, just one paragraph. Abstract includes the background or importance of community service topics, devotion goals, service partners, service methods and service results. If you use this template correctly, all numbering will be generated automatically. So you don't need to edit it manually. Of course, if you create a section of this paper that requires numbering after this template, the number will continue with the existing part number. Once again, you don't need to edit the part numbers, because if the contents of this template are deleted, the numbers will be sorted by themselves. If you want to try to delete the contents of this template, please back up first.